Morphology study of nanoporous black TiOx synthesized by laser‐based method. Issue 7 (7th March 2017) - Cacciato, G.; Zimbone, M.; Ruffino, F.; Privitera, V.; Grimaldi, M. G.
Abstract : In this work, we analyse and discuss the morphology evolution of black TiO x film formed on the surface of a titanium foil following the 1064 nm wavelength nanosecond pulsed laser irradiation in water. The nanostructure of the film depends on the number of laser pulses N and laser fluence F . We interpreted the experimental observations in terms of accumulated fluence F A, obtained as the product of N and F . We showed that the nanoporous morphology of this material occurs above a specific F A threshold of about 100 J / cm −2 .